O Vestibular da UFC. Implicações para o Ensino Médio: um estudo de caso a partir das mudanças realizadas de 1978 a 2004 - Silva, João Eudes Moreira da (2007)
This study intends to investigate changes brought about in the College Entrance Examinations (Vestibular) of the Universidade Federal do Ceará (UFC) in the last 26 years and its effects in the Brazilian Secondary Education. Specifically, the explanations for several modifications established - each at a different time and manner - are analyzed based on interviews with presidents and vice-presidents of the Examination’s Coordination Committee (CCV). Through the speech of the teachers responsible for the elaboration of the Biology tests, the impact of the vestibular exams are revealed as well as the effects in the subjects dealt with in Secondary School. This investigation confirms the historicity of the change process by utilizing documents from the Education, Research and Community Service Council (CEPE) and the Call for Exams Publications from 1978 to 2007. This qualitative research chose a semi-structured interview and document analysis as tools for data survey, focusing especially on the sayings of the presidents and vice-presidents of the CCV related to the changes that took place in UFC’s Vestibular examinations from 1978 to 2007; the sayings of teachers who developed the Biology tests in he UFC Vestibular; as well as on documental analysis of these Biology tests and official documents. In the text, the ability of private schools to adapt to the innovations proposed by the CCV is highlighted and the lack of visibility of these actions by public schools is noticed. It is concluded that the access system to the university has an indisputable influence in Secondary School, both in content and in its epistemological approach, however this influence can only be positive if there is a convergence between the access system to Higher Education and the objectives in Secondary School itself. It is shown that UFC needs to review its selection criteria, resize the contents required and invert the way it contributes with the evaluation process, centralizing its concerns in the construction of an educational proposal that may shape individuals capable of thinking, proposing and making changes that can transform the course of history.